(untitled) (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: The objectives of this investigation were to develop gastroretentive floating bioadhesive drug delivery for simvastatin to increase gastric residence time and reduce the dose frequency. To explore Badams gum’s sticking property in floating bioadhesive drug delivery of simvastatin. Materials and Methods: Floating bioadhesive tablet was formulated with Badam gum and hydroxypropyl methylcellulose (HPMC) K 15 M polymers, sodium bicarbonate, and citric acid as the gas generating agents to reduce floating lag time. Tablets were prepared by direct compression method. Optimization study was conducted using 32 factorial design. The concentration of polymers was considered as independent variables whereas swelling index, bioadhesive strength and % drug release at 10 h, of the tablets were utilized as dependent variables. Results and Discussions: Preformulation study suggests powders blends shows acceptable flow properties. Simvastatin floating- bioadhesive tablet found to be good without chipping, capping, and sticking. Comparing all the formulations, A5 optimized formulation exhibited 98.10 ± 2.10% of drug release in 12 h, floating lag time of 34 ± 3 s, with appropriate bioadhesive property, and total floating time of over 12 h. It was observed that increasing percentage of polymer in formulation the drug release decreased. Developed formulations were stable during stability studies. Conclusion: Based on these findings, it was concluded that Badam gum can be used as a bioadhesive as well as release retarding polymer for the floating bioadhesive dosage form of other drugs.